2018
DOI: 10.1111/trf.14833
|View full text |Cite
|
Sign up to set email alerts
|

In vivo viability of extended 4°C‐stored autologous apheresis platelets

Abstract: While the in vitro variables suggest largely comparable results between plasma and PASs, in vivo recoveries were higher with plasma compared with both Intersol and Isoplate (p = 0.057 and p = 0.002, respectively). Whether this difference leads to clinically relevant differences in hemostatic efficacy remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 19 publications
3
55
0
1
Order By: Relevance
“…10 This study also suggested that there could be a benefit to plasma as storage medium. 10 Based on the 5-to 7-day storage limit for RT-stored platelets, we decided to store platelets in the 4°C test group for 5 days and increase the storage time up to 20 days to exceed our longest previous storage time. Moreover, other groups have published on in vitro performance of 21-day cold-stored platelets in the past and suggested acceptable in vitro performance.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…10 This study also suggested that there could be a benefit to plasma as storage medium. 10 Based on the 5-to 7-day storage limit for RT-stored platelets, we decided to store platelets in the 4°C test group for 5 days and increase the storage time up to 20 days to exceed our longest previous storage time. Moreover, other groups have published on in vitro performance of 21-day cold-stored platelets in the past and suggested acceptable in vitro performance.…”
Section: Discussionmentioning
confidence: 70%
“…To validate 20‐day cold‐ and plasma‐stored platelets as a transfusion product, we stored platelets in plasma 5, 10, 15, and 20 days at 4°C and included a fresh and 5‐ or 7‐day RT comparator. We had previously published results on 3‐day cold‐stored platelets and compared them to platelets stored at 4°C for 10 and 15 days, respectively . This study also suggested that there could be a benefit to plasma as storage medium .…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…All these solutions contain varying combinations of citrate, phosphate, acetate, magnesium, potassium, gluconate, and glucose, and the ingredients synergistically act to provide anticoagulation, membrane stabilization, metabolic substrates, buffering activity, apoptosis inhibition, and activation inhibition . Recent data has noted that COLD‐PLTs collected and stored in PAS‐F may be significantly superior in in vitro functional assays than PAS‐C–stored COLD‐PLTs, especially when analyzed for their ability to adhere to collagen under flow conditions, although their survival may be inferior to the PAS‐C–stored COLD‐PLTs …”
Section: Cold Pltsmentioning
confidence: 99%
“…33,35 Recent data has noted that COLD-PLTs collected and stored in PAS-F may be significantly superior in in vitro functional assays than PAS-C-stored COLD-PLTs, especially when analyzed for their ability to adhere to collagen under flow conditions, 35 although their survival may be inferior to the PAS-C-stored COLD-PLTs. 36 Several novel additives to PLT storage media are under investigation. These solutions aim to attenuate the storage lesions by reversibly inhibiting PLT activation, preventing the changes in pH and lactate associated with glycolysis, or reducing the risk of pathogen contamination.…”
Section: Cold Pltsmentioning
confidence: 99%